1989
DOI: 10.1159/000242908
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation during Morphogenesis of the Human Colon

Abstract: Cell proliferation during morphogenesis of human colon from 8 to 18 weeks of gestation was investigated using radioautography. The sites of [3H]-thymidine uptake were localized in the epithelium, the mesenchyme, and the muscularis externa. As long as the epithelium was stratified, the proliferative pool was very large, and the highest labeling indices (up to 28%) were found during this period. With the formation of villi, the proliferative pool decreased and focused exclusively in the developing cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…We also found in this study that DNA synthesis in the lower half of the crypts was greater than in the superficial half of the crypts, and the same tendency has also been reported in small intestine (Leblond and Messier, 1958) and colon (Arsenault and MCnard, 1989;Minard and Arsenault, 1987;Eastwood and Trier, 1974;Chang and Leblond, 1971a.b) by [3H]-thymidine autoradiography. The observations suggested that renewal and replacement of mouse cecal epithelium continues from the fetal stage to senescence and that the cells of cecal epithelium were renewed continuously by production of new cells in the bases of the crypts to replace the numbers of superficial cells lost near the lumen (Chang, 1971;Leblond and Messier, 1958).…”
Section: Discussionsupporting
confidence: 88%
“…We also found in this study that DNA synthesis in the lower half of the crypts was greater than in the superficial half of the crypts, and the same tendency has also been reported in small intestine (Leblond and Messier, 1958) and colon (Arsenault and MCnard, 1989;Minard and Arsenault, 1987;Eastwood and Trier, 1974;Chang and Leblond, 1971a.b) by [3H]-thymidine autoradiography. The observations suggested that renewal and replacement of mouse cecal epithelium continues from the fetal stage to senescence and that the cells of cecal epithelium were renewed continuously by production of new cells in the bases of the crypts to replace the numbers of superficial cells lost near the lumen (Chang, 1971;Leblond and Messier, 1958).…”
Section: Discussionsupporting
confidence: 88%
“…The labeling indices were determined to establish whether insulin (3 mU/ml) affected the proliferation at the epithelial cell levels (table 1). The incorporation of the radioactive precursor occured mainly in the epithelium and to a lesser degree in the mesenchyme and muscular layers, as expected [23,24]. The labeling index was significantly higher in insulin-treated explants (p !…”
Section: Resultssupporting
confidence: 57%
“…All results were expressed as disintegrations per minute per microgram of DNA. Selected tissues were fixed and embedded in Epon as previously described [23,24]. The sections (1 Ìm) were mounted on glass slides and stained with aldehyde fuchsin.…”
Section: Dna Synthesis and Radioautographymentioning
confidence: 99%
“…~9 0 ; 170. firmed the confinement of proliferating cells in cell aggregates distributed over the mouse mucosal folds and that these aggregates are the precursors of the cryptlike invaginations already seen between 2 and 4 days after birth. In human fetal colon, which develops true villus structures, such distribution of proliferating cells was never seen, as [3Hl-thymidine labeled cells were always located in the developing crypts at the base of the villi (Arsenault and Menard, 1989). While the proliferative pool occupies the midcrypt portion in the proximal colon, it is mainly located at the base of the crypt in the distal colon.…”
Section: Discussionmentioning
confidence: 98%